Metalworking Milling Maintenance Priorities Using MTBF and FMEA: Prioritas Pemeliharaan Mesin Penggilingan Logam Menggunakan MTBF dan FMEA - Santoso, Muhammad Rakha Anargya; Rusindiyanto, Rusindiyanto (Academia Open, 2026)
General Background Machine reliability is essential in metalworking industries because production continuity depends on high-precision equipment that can operate with minimal downtime. Specific Background The observed universal milling machine experienced frequent breakdowns that interrupted production activities, indicating that its existing care system was not fully planned or documented. Knowledge Gap Although previous studies have applied reliability-based approaches to industrial equipment, the specific integration of Mean Time Between Failure and Failure Mode and Effect Analysis for determining component-level repair ranking and scheduled care on the observed universal milling machine remains necessary. Aims This study aims to identify failure causes, determine repair ranking, and design a preventive schedule for universal milling machine components. Results The analysis identified worn gears and unresponsive panels as the most critical failures, each recording the highest Risk Priority Number of 576. MTBF calculation produced different component intervals, including gears every 7 days, panels every 22 days, automatic pins every 36 days, transformers every 90 days, fan every 180 days, and vanbelt and automatic bearing every 60 days. Availability results showed the lowest readiness for gears at 88.8%, while other components remained above 97%. Novelty This study combines RPN-based failure ranking with MTBF-based interval planning for a 42-year-old universal milling machine. Implications The findings provide a practical basis for structured preventive scheduling and targeted component repair in metalworking operations. Highlights: Worn gears and unresponsive panels recorded the highest RPN value of 576. Component care intervals ranged from 7 to 180 days. Gear readiness reached the lowest value at 88.8%. Keywords: FMEA, MTBF, Maintenance, Universal Milling